COMPLETELY EDENTULOUS PATIENTS. PART 2: ALVEOLAR RIDGE HEIGHT VALUES FROM INTRA- AND EXTRA-ORAL MEASUREMENTS - Nickolay Apostolov; Stefan Zlatev; Elitsa Deliverska; Rangel Todorov (Peytchinski Publishing, 2022)
Aim: The aim of the present research is to assess the distribution of the alveolar ridge height (ARH) and compare the values obtained intraorally and from plaster, master-casts poured from two-step final impressions. Materials and methods: For the purpose of this study, 96 patients aged 49-88 were examined between 2016-2019. The research was conducted during the practical classes in prosthetic dental medicine and oral and maxillo-facial surgery at the Faculty of Dental Medicine, Medical University - Sofia. The study methods included an individual interview, observation, palpation, and clinical and laboratory measurements of the ARH in predefined locations. The results were collected in pre-made patientcards. The investigated variables were age, gender, and height of the alveolar ridges in the frontal and distal areas for the upper and lower jaws. Results: The intra oral measurements showed a mean 8.64±2.6mm height of the entire upper jaw with the highest average value obtained in the frontal area - 9.48±2.67 mm. Both distal areas were with comparable heights, demonstrating similar results to the frontal segment, which suggests equability in the atrophic maxilla for our sample. For the entire lower jaw, the intraoral measurements showed a mean score of 4.32±2.09 mm. A similar tendency was observed for the frontal - 5.08±2.20 mm and both distal areas, but with a more pronounced difference between them. There was a significant difference between the intra- and extra-oral measurements averaging at 0.77±68 mm across all values.